The Effect of The Application of Reciprocal Teaching Strategy (RTS) and Reading Motivation Towards The Eighth Grade Students’ Reading Ability at Junior High School 35 Palembang - Aprilia, Ifrohati; Simaibang, Baginda; Mulyadi, Mulyadi (Jurnal Pendidikan Tambusai, 2021)
Reciprocal teaching strategy (RTS) is an instructional activity that takes text from of dialogue between teachers and students regrinding segments of the text for the purpose of constructing the meaning of text. A reciprocal provides students with four specific reading strategies that are actively and consciously used to support comprehension; questioning, clarifying, summarizing, and predicting. Reading is an activity that is done by written text or print text as a medium. In this activity readers decode and interpret the language to get the meaning. This study aims to determine student reading motivation towards reciprocal teaching strategy on the eight grade students’ reading ability at Junior High School 35 Palembang.